2014
DOI: 10.1159/000360857
|View full text |Cite
|
Sign up to set email alerts
|

Whole Exome Sequencing to Identify Genetic Causes of Short Stature

Abstract: Background/Aims: Short stature is a common reason for presentation to pediatric endocrinology clinics. However, for most patients, no cause for the short stature can be identified. As genetics plays a strong role in height, we sought to identify known and novel genetic causes of short stature. Methods: We recruited 14 children with severe short stature of unknown etiology. We conducted whole exome sequencing of the patients and their family members. We used an analysis pipeline to identify rare non-synonymous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
68
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 28 publications
4
68
0
3
Order By: Relevance
“…In the first decade of the 21st century, the genetic toolbox was expanded by whole genome single nucleotide polymorphism (SNP) array (1) and array-comparative genomic hybridization (array-CGH) (2) for the detection of microdeletions or microduplications (copy number variants (CNVs)), the former of which is also able to detect uniparental disomy. In the second decade an even more successful tool became available -whole exome sequencing (WES) -for the detection of gene variants as possible causes of congenital disorders (3,4,5,6), with a good diagnostic yield in well-selected patients (6). In general, WES is performed in an index patient and his/her parents (a 'trio'), and (if available) affected and non-affected siblings, to limit the number of informative variants in the bioinformatic analysis.…”
Section: Introductionmentioning
confidence: 99%
“…In the first decade of the 21st century, the genetic toolbox was expanded by whole genome single nucleotide polymorphism (SNP) array (1) and array-comparative genomic hybridization (array-CGH) (2) for the detection of microdeletions or microduplications (copy number variants (CNVs)), the former of which is also able to detect uniparental disomy. In the second decade an even more successful tool became available -whole exome sequencing (WES) -for the detection of gene variants as possible causes of congenital disorders (3,4,5,6), with a good diagnostic yield in well-selected patients (6). In general, WES is performed in an index patient and his/her parents (a 'trio'), and (if available) affected and non-affected siblings, to limit the number of informative variants in the bioinformatic analysis.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is some evidence to suggest that exome sequencing will identify a monogenic cause in patients with more severe short stature or those with syn- dromic features. Our group, for example, previously found a genetic etiology in 5 out of 14 patients with severe syndromic short stature who underwent exome sequencing [2]. The current study focused on patients with severe primary IGF-I deficiency, a subgroup of growth disorders which one would posit to have a higher likelihood of monogenic causes, especially since human mutations have been found in multiple genes in the growth hormone/IGF-I axis [3].…”
Section: Doi: 101159/000481285mentioning
confidence: 98%
“…The price of WES is dropping, and our ability to rapidly filter the background ‘noise' of inconsequential genetic variants is improving. With additional studies of WES in larger groups, some of the ‘maybes' found by Guo et al [1] in this population will become definitive diagnoses and WES will become routine in the evaluation of short stature.…”
mentioning
confidence: 94%
“…In this issue, Guo et al [1] describe the results of whole exome sequencing (WES) in 14 patients like the one described above. They sought rare, highly penetrant, monogenic variants as potential explanations for each patient's condition.…”
mentioning
confidence: 99%
See 1 more Smart Citation